Reliability Analysis of Medical Imaging Systems Based on Observer Studies - Goin, J. E.; Cook, L. T.; Fritz, S. L. (Methods of Information in Medicine, 1983)
Statistical methodology is presented which can be used in analyzing the reliability of diagnostic imaging systems in differential diagnosis situations. A reliability criterion is developed along with formulas for estimating its large sample variance. Several hypothetical examples are given to illustrate the methodology.
Keywords: Diagnostic Imaging; Reliability Analysis; Kappa Statistic; Information Theory; Diagnostic Accuracy; Diagnostic Reproducibility